Impact of clinical decision support on empirical antibiotic prescribing for children with community-acquired pneumonia - Mostaghim, M.; Snelling, Thomas; McMullan, B.; Ewe, Y.; Bajorek, B. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Paediatrics and Child Health Division (The Royal Australasian College of Physicians) Aim: To assess the impact of a computerised clinical decision support system (CDSS) on antibiotic use in hospitalised children with a presumptive diagnosis of uncomplicated community-acquired pneumonia (CAP). Methods: Codes associated with lower respiratory tract infection were used to identify cases of presumed uncomplicated CAP requiring admission to a tertiary paediatric hospital. Random sampling of the periods between 1 October 2010 and 30 September 2012 (pre-CDSS) and 1 October 2012 and 30 September 2014 (post-CDSS) determined the sequence of case assessment by two independent investigators. Initial antibiotic therapy, associated CDSS approvals and documented signs of clinical deterioration prior to antibiotic decision-making were recorded. Results: Statistically significant differences between cases pre- and post-CDSS implementation were minimal. High fever was observed in 57.5% (77/134) cases pre-CDSS and 45.8% (49/107) cases post-CDSS (P = 0.07). Supplemental oxygen was used in 30.6% pre-CDSS and 54.2% post-CDSS cases (P < 0.001). Narrow-spectrum penicillins were prescribed most often, with no statistically significant change post-CDSS implementation (81.3% pre-CDSS, 77.6% post-CDSS, P = 0.47). Macrolides were used consistently throughout the study period (53.7% pre-CDSS, 61.7% post-CDSS; P = 0.21). Conclusion: CDSS implementation did not reduce already low rates of broad-spectrum antibiotic use for uncomplicated CAP.